Strength improvement of jelutong (Dyera costulata) wood via phenolic resin treatments - Ashaari, Zaidon; Seng, Hua Lee; Mustamel, Maizatul Nurain; Mohd Salleh, Nor Farahida (Springer Verlag, 2015)
The objective of this study was to evaluate the effects of phenolic resin treatment on the strength improvement of jelutong wood. 30 % low molecular weight phenol formaldehyde resin (LmwPF) was used as treating solution. 30 % urea was incorporated into LmwPF resin to serve as the second type of treating solution. Impregnated and compregnated jelutong wood were produced using these two treating solutions. For compregnation process, 3 compression ratios (40, 60 and 80 %) were applied. A set of untreated jelutong wood was served as control. Formaldehyde emission, strength properties and specific strengths of the wood samples were evaluated. The results showed that the addition of urea had effectively reduced the formaldehyde emitted from the treated wood. No significant reduction in strength was reported accompanying by the addition of urea. Both density and mechanical properties of the compregnated wood are highly dependent on the compression ratio. Higher compression (lower CR) produced wood with higher density and modulus of rupture. In conclusion, phenolic resin treatments were found successfully enhanced the strength properties of jelutong wood.